Effectiveness of Dexamethasone for Prevention of Intraoperative Shivering in Caesarean Delivery Under Subarachnoid Block - Pradhan, Roshan; Mishra, Seema Kumari; Khanal, Kanak (Birat Journal of Health Sciences, 2020)
Introduction: Shivering is frequently seen after subarachnoid block. Subarachnoid block impairs the thermoregulation system by inhibiting tonic vasoconstriction with redistribution of blood flow and core heat from the trunk to the peripheral tissue. Intraoperative shivering leads to increase in oxygen consumption and carbon dioxide production. This causes an increase in heart rate, blood pressure resulting in exacerbation of ischemic heart disease, increased risk of hypoxemia, intraocular pressure, intracranial pressure, metabolic rate, lactic acidosis, pain at the surgical site and discomfort to the patient. Objective: To assess the effectiveness of Dexamethasone in preventing intraoperative shivering in patients of cesarean delivery under subarachnoid block. Methodology: This was a hospital based prospective, comparative, cross sectional study which was conducted from February 2019 to July 2019 among 88 pregnant patients of age group 18 to 35 years old, American Society of Anesthesiologists (ASA) physical status 1 and 2, posted for elective or emergency caesarean delivery at Birat Medical College and Teaching Hospital (BMCTH). Operation room temperature was recorded by a wall thermometer and maintained during surgery between 20 to 25 degree Celsius and intravenous fluids were kept at this temperature. Patients were divided into two equal groups. Group S (study group) patients received 2 ml or 8mg of dexamethasone IV (As a premedication before giving subarachnoid block) while group C (control group) patients received 2 ml of normal saline. If the patients shivered according to classification of shivering, the prophylaxis was regarded as ineffective. Results: Patients undergoing caesarean delivery under subarachnoid block had significantly reduced (p value = 0.002) intraopera tive shivering who received prophylactic dexamethasone (group S). Conclusion: The prophylactic use of 8mg i.v dexamethasone was significant in prevention of shivering in Nepalese population who underwent caesarean delivery under subarachnoid block.